Simulation and Experimental Investigation on Carbonized Tracking Failure of EPDM/BN-Based Electrical Insulation - Nazir, Muhammad Tariq (Polymers (Basel), 2020)
Ethylene propylene diene monomer (EPDM) is broadly employed as an insulating material for high voltage applications. Surface discharge-induced thermal depolymerization and carbon tracking adversely affect its performance. This work reports the electrical field modeling, carbon tracking lifetime, infrared thermal distribution, and leakage current development on EPDM-based insulation with the addition of nano-BN (boron nitride) contents. Melt mixing and compression molding techniques were used for the fabrication of nanocomposites. An electrical tracking resistance test was carried out as per IEC-60587. Simulation results show that contamination significantly distorted the electrical field distribution and induced dry band arcing. Experimental results indicate that electric field stress was noticed significantly higher at the intersection of insulation and edges of the area of contamination. Moreover, the field substantially intensified with the increasing voltage levels. Experimental results show improved carbonized tracking lifetime with the addition of nano-BN contents. Furthermore, surface temperature was reduced in the critical contamination flow path. The third harmonic component in the leakage current declined with the increase of the nano-BN contents. It is concluded that addition of nano-BN imparts a better tracking failure time, and this is attributed to better thermal conductivity and thermal stability, as well as an improved shielding effect to electrical discharges on the surface of nanocomposite insulators.